Strengths and difficulties of school-aged children in the family and school context - Μπίμπου-Νάκου Ιωάννα; Κιοσέογλου Γρηγόρης; Στογιαννίδου Αριάδνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF